Biocoal Characterization as an Environmentally Friendly Alternative Energy Innovation Composite Variations of Gasified Char with Coconut Shell Charcoal - Aria Yopianita; Aida Syarif; Muhammad Yerizam; Rusdianasari Rusdianasari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
In accordance with the mandate of the Regulation of the Indonesian Minister of Energy and Mineral Resources for the use of cleaner coal through coal gasification projects, in the future the coal gasification industry will produce char as a by-product. This study aims to characterize coal gasification char using a prototype underground coal gasification (UCG) and the addition of coconut shell charcoal biomass as a raw material for making biobriquettes. By using coal as raw material from the Muara Tiga Besar Mine of PT Bukit Asam, five kinds of coal samples from different layers were obtained, which from the characterization results, both coal and char, did not have too significant deviations so that the research variables could be ignored. The results of the characterization of char from coal gasification results compared to the initial sample of coal showed an increase in calorific value, a decrease in sulfur content and a significant decrease in water content, so it can be concluded that char from coal gasification has good potential as a raw material for biobriquettes. By using char and coconut shell charcoal with the ratio of variations in the composition of char and coconut shell compositions is 100%:0%; 75%:25%; 50%:50%; 25%:75% and 0%:100% carried out the briquetting process. The results of the biobriquette characterization met the criteria of the Indonesian National Standard (SNI) 01-6235-2000 and Minister of Energy and Mineral Resources regulation No. 047 of 2006